2012
DOI: 10.1177/097185241201600204
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gender Socialization of Adolescent Boys in Single-mother Households: Perspectives from a Community in Cape Town, South Africa

Abstract: This article analyzes the gender socialization patterns and masculine constructions of a group of adolescent boys living in single-mother households. Data collection methods such as observation and interviews were employed together with interpretive techniques to explain how the participants constructed their realities based on their experiences. The results revealed that gender socialization of adolescent boys took place when their single mothers-pressured by dramatic physical changes in their adolescent sons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…McHale et al (2000) note that as adolescents go through the process of identity formation and trying to assert their independence from their parents they may encounter strains in their relationships with the parents. Bojuwoye et al (2012) also report that adolescent boys in single-mother households often find communication with their oppositesex parents very difficult. Generally conflict with parents is a key process of adolescence, as both parents and adolescents simultaneously negotiate changes in the relationships resulting from transition through adolescence (Updegraff, Delgado and Wheeler, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McHale et al (2000) note that as adolescents go through the process of identity formation and trying to assert their independence from their parents they may encounter strains in their relationships with the parents. Bojuwoye et al (2012) also report that adolescent boys in single-mother households often find communication with their oppositesex parents very difficult. Generally conflict with parents is a key process of adolescence, as both parents and adolescents simultaneously negotiate changes in the relationships resulting from transition through adolescence (Updegraff, Delgado and Wheeler, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Laftman (2010) found children in single-mother households to have lower social support from parents and fewer material resources hence their poorer health conditions in comparison with children living with two original parents. One explanation for the participants' reported dissatisfaction with the social support within their single-mother households may be because of the stage of physical development of the participants who being adolescents were in search of their identity (male identity for that matter) which cause them to experience conflicts with their opposite-sex parents (their mothers) (Bojuwoye, & Sylvester, 2012). McHale et al (2000) note that as adolescents go through the process of identity formation and trying to assert their independence from their parents they may encounter strains in their relationships with the parents.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived social acceptability of tobacco use, perceived harm, and education about tobacco harm Many African societies are male-dominant with distinct patterns of gender socialization 18,19 . The perceived ethnographic significance of smoking at social gatherings may therefore differ between boys and girls.…”
Section: Indicators Of Pro-tobacco Social Influencesmentioning
confidence: 99%
“…Examining gender differences in youth tobacco use is further important as it aligns tobacco control within the context of broader human development goals seeking to eliminate gender inequalities 18 . Gender disparities are well documented for other public health problems in Africa, including HIV/AIDS and child illiteracy 19 . There is, however, a paucity of data on the African continent regarding gender differences in youth tobacco use and what new trends might be emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Societal views and beliefs about gender are strongly influenced and mediated by cultural beliefs that are appropriated during social interactions. A study conducted on boys' perceptions of gender in a South African high school found that cultural values and beliefs reflect the earlier socialization of children into different roles (Bojuwoye & Sylvester, 2012;Carter, 2014).…”
Section: Society As Agent Of Socializationmentioning
confidence: 99%